Perspectives of Migration in India - Mondal, Sayan; Singh, B. N. (National Geographical Journal of India, 2022)
In the present paper, an attempt has been made to analyse the migration status of population in India from the perspectives of demography, economic and social reasons. Movement is an integral part of the human life and civilization dated back over five thousand years. Human migration is mainly induced due to various reasons like searching for foods, searching for habitable places in a hostile environment, searching for better lifestyles, relief from the civil disobedience and wars etc. from the early age of civilization. Due to the physical vastness and cultural variation across various regions, India experiences also some different types of migration. The developmental plans by the various governments after the post-colonial era were also influenced differently on the migration scenario in India. The present study emphasizes on various aspect of migration scenario and their perspectives from geographical point of view. The major sources of data for this paper are from Census of India and the NSSO reports.